Percieved Psychosocial Factors as Determinants of Drug Use and Abuse among Public Secondary School Youths in Osun State, Nigeria - Taiwo, Sanni, Kamorudeen; Olayemi, Aransi, Waliyi (American Journal of Education and Learning, 2019)
Youths comprise the huge percentage of the world population. This stage is mostly influenced by social interaction with peer group, access to social media, parental background among others. In the light of this, the study was designed to investigate perceived psychosocial factors as determinants of drug use and abuse among public secondary schools youths in Osun State, Nigeria. The survey research design was adopted and simple random sampling technique was used to select two-hundred (200) participants. The research instrument tagged ‘Perceived Psychosocial Factors on Drug Questionnaire (PPFDQ) was used for data collection. The gathered data were analysed with the aid of inferential and descriptive statistical tools. The empirical outcomes indicated that family influence, peer group, gender quality, traumatic life events and frustrations, availability and accessibility as well as media roles are some of the perceived psychosocial factors that influenced youths’ drug use and abuse and that the religious inclination and gender traits of the youth was insignificant to the patterns and problems connected with drug use and abuse among them. Establishment of counselling unit within the school, avoidance of over castigation on academic performance by parents and teachers and maintenance of religious standard to mention a few were suggested in terms of recommendations.